Pengaruh Disposisi Produktif terhadap Kemampuan Pemahaman Instrumental Mahasiswa - Rahmadeni, Fevi; Rahmawati, Arbingatu; Rahma Wanti, Meta Putri (ARITHMETIC: Academic Journal of Math, 2024)
This study aim to see the effect of Productive Disposition on Students' Instrumental Understanding Ability. The subjects of the study were students of the Arabic Language Education Study Program in Semester III who took the Educational Statistics Course. The subjects of the study were students of the Arabic Language Education Study Program in Semester 3 who took the Educational Statistics Course. The study used quantitative research. The data collection technique used the Productive Disposition Questionnaire and the Student Instrumental Understanding Ability Test. The results of the study showed that there was a positive relationship between Productive Disposition and Students' Instrumental Understanding Ability with a Pearson correlation of 0.838. Furthermore, the simple regression hypothesis test showed that there was a significant effect of Productive Disposition on Students' Instrumental Understanding Ability with the regression equation y=-33,059+1,173x. The conclusion of the study shows that there is a significant influence of Productive Disposition on Students' Instrumental Understanding Ability. Therefore, it is expected that lecturers can create learning that supports the improvement of Productive Disposition so that students' instrumental understanding ability becomes better.